Earthquake anxiety and sleep quality among adolescent survivors 9–12 months after the great earthquakes in Türkiye: a cross-sectional study - Ayşe Kahraman; Emine Çubukcu (Scientific Reports, 2025)
Abstract This study investigated the relationship between earthquake-related anxiety and sleep quality among adolescents affected by a major earthquake in Türkiye. An analytical cross-sectional design was employed, involving 402 adolescents aged 12–18 years from Kahramanmaraş, Kilis, Diyarbakır, Adana, Osmaniye, Gaziantep, Şanlıurfa, Adıyaman, Malatya, and Hatay provinces who continued to live in Hatay. Participants were selected through purposive sampling. Data collection tools included the Adolescent Descriptive Characteristics Form, Earthquake Anxiety Scale, and Pittsburgh Sleep Quality Index. Data were evaluated using descriptive statistical analyses, chi-square test, and logistic regression analysis. The chi-square test was used to evaluate the categorical variables affecting earthquake anxiety and sleep quality. The relationship between the numerical scores of the two scales was calculated by Spearman’s rho correlation coefficient. The mean age of the adolescents was 14.01 ± 1.70 years, with 52.5% female participants and 98% living in containers. 65.7% reported sleeping less than 7 h per night. The mean Earthquake Anxiety Scale score was 119.40 ± 28.13, and the mean Pittsburgh Sleep Quality Index score was 9.28 ± 4.26. High earthquake anxiety was observed in 89.4% of adolescents with poor sleep quality (χ² = 38.884, p < 0.001). Adolescents affected by the earthquake exhibited high anxiety levels and impaired sleep quality, with a clear correlation between increased earthquake anxiety and deteriorating sleep quality.